Causes and consequences of tipping points in river delta social–ecological systems - Cai Ladd (Ambio, 2024)
The sustainability of social-ecological systems within river deltas globally is in question as rapid development and environmental change trigger "negative” or “positive” tipping points depending on actors’ perspectives, e.g., regime shift from abundant sediment deposition to sediment shortage, agricultural sustainability to agricultural collapse or shift from rural to urban land. Using a systematic review of the literature, we show how cascading effects across anthropogenic, ecological, and geophysical processes have triggered numerous tipping points in the governance, hydrological and land use management of the world’s river deltas. Crossing tipping points had both positive and negative effects that generally enhanced economic development to the detriment of the environment. Assessment of deltas that featured prominently in the review revealed how outcomes of tipping points can inform the long-term trajectory of deltas towards sustainability or collapse. Management of key drivers at the delta scale can trigger positive tipping points to place social-ecological systems on a pathway towards sustainable development.